'The times are changing': New Zealand smokers' perceptions of the tobacco endgame. Issue 6 (16th June 2012) - Maubach, Ninya; Hoek, Janet A; Edwards, Richard; Gifford, Heather; Erick, Stephanie; Newcombe, Rhiannon
Abstract : Background: The New Zealand government's goal of achieving a smoke-free society by 2025 reflects growing interest in 'endgame' solutions to tobacco smoking. However, tobacco companies have framed 'endgame' strategies as contrary to individual freedoms and 'choice'; these claims heighten politicians' sensitivity to 'nanny state' allegations and may undermine tobacco control policies. Public support for stronger policies could strengthen political will; however, little is known about how smokers perceive endgame scenarios or the factors underlying their support or opposition to these. Methods: The authors conducted 47 in-depth interviews with four priority groups: Māori, Pacific, young adults and pregnant women; all were smokers or very recent quitters. The authors used thematic analysis to interpret the transcripts. Results: Most participants strongly supported the 2025 smoke-free goal, recognised the broader social good that would result and accepted the personal inconvenience of quitting. Yet they wanted to retain control over when and how they would quit and asserted their 'freedom' to smoke. Participants identified interventions that would extend current policy and maintain the autonomy they valued; the authors classified these into four themes: restricting supply, diminishing visibility, decreasing availability and affordability, and increasing quit support. Conclusions: Politicians may have a stronger mandate to implement endgame policies than they appreciate. Participants' use of industry arguments when asserting their freedom to 'choose' to smoke and quit suggests a need for denormalisation strategies that challenge industry propaganda, demonstrate how endgame measures would empower smokers and re-iterate the community benefits a smoke-free society will deliver.